Profil Vulva dan Suhu Tubuh Kambing Peranakan Etawa pada Sinkronisasi Estrus Menggunakan Medroxy Progesterone Acetate dan Suplementasi Zinc (Zn) - Muhammad Rosyid Ridlo; Risa Ummami; Naela Wanda Yusria Dalimunthe; Dhasia Ramandani; Nur Ika Prihanani; Morsid Andityas; Tri Satya Mastuti Widi (Penelitian dan Pengabdian Kepada Masyarakat Sekolah Vokasi Universitas Gadjah Mada, 2018)
Peranakan Etawa (PE) goat farming is one of the growing livestock sectors in Indonesia. Indonesia needs a sustainable breeding system that can guarantee the availability of goats. Estrus synchronization is a necessity that can help uniform the breeding time and manage the time of pregnancy and birth. Artificial estrus synchronization techniques that use a combination of Prosterone and Zinc minerals give good results of estrus synchronization in goats. The Aim of this research is to understand the combination efectiveness of estrus synchronization technique with progesterone acetate and Zinc supplementation. The design of this study used two treatment groups, each group consisting of three does PE goats. Estrus synchronization of experimental animals in treatment 1 and 2 was carried out using polyurethane sponge implant method which contained medroxi progesterone acetate 60 mg. Group 1 was given Sponge Progesterone for nine 9 days while giving Zinc (Zn) mineral supplement (Elemental Zn 20 mg, Kimia Farma) orally given 7 times. The frequency of Zinc administration every day begins during intra vaginal sponge insertion. Group 2 was treated same as group 1 with 14 days of implant time and 7 times of Zinc supplementation.The results showed that both treatments occurred estrus simultaneously with good estrus quality. Both treatments show the results of the estrus 8 score assessment with the estrus 3-9 range. The maximum estrus quality’s value of group 2 was higher (8.33 ± 0.57) compared to group 1 (8.0 ± 1.0). The estrus duration of group 2 occurs for 24 hours and group 1 for 7 hours. Estrus onset of Group 2 is earlier (58 hours) than group 1 (75 hours). Both treatment groups showed an increase in temperature at period of the occurrence of estrus. Body temperature during estrus time was 38.7 ± 0.20 0C to 39.60 ± 0.26 0C. The conclusion of this study is that in both treatments of estrus synchronization using sponge progesterone and zinc supplementation can cause estrus synchronization effectively . The duration of estrus in group 1 (9 days of implant) was Shorter than group 2 (14 days of implant). The onset of estrus time of group 1 (9 days of implant) was longer than Group 2 (14 days of implant). The body temperature of the experimental animals increases with the occurrence of estrus.